Level of awareness on waqf among muslims in Ampang, Selangor / Ahmad Nazirul Na'im Ahmad Shuhaimi - Ahmad Shuhaimi, Ahmad Nazirul Na'im (2019)
Waqf is an important component in a trusted Islamic economic instrument, can solving socioeconomic problems especially in efforts to eliminate poverty due to shortage income and employment. Lack of inherent knowledge about waqf is one of one key factor affecting waqf institutions around the word and especially in Malaysia. As studies have shown majority of muslim have limited knowledge about waqf and its practice. Most of the people tend to prefer the classical practice of waqf since that is what they are familiar with. From the survey made by MAIS in 2008, almost 70 per cent of Muslims in Malaysia do not aware on Saham Waqf done by the institution (Noor Aimi Bt Mohd Puad, 2014). Researcher had achieve the research objective in this study. There are to identify the overall perception on awareness on waqf. The second one is to find out the factors on the lack of awareness of waqf among Muslims in Malaysia and the last to propose suggestions on how to improve the awareness on waqf among Muslims. Researcher is using a primary data in the get a feedback and responds from the respondent. Primary data is the data that is collected through the interviews and the question surveys. It is also known as the first-hand data. In this research, the data are being collected through question surveys. The questionnaire will be printed and distributed to the respondents. The questionnaires are being chosen to be used in this research because if compared to interviews, the questionnaires are capable to reach out a large number of respondents in a short period of time. Besides, using the questionnaires are also cheaper and can save more time compare to the other data collection method.